Modalidades de gestión de financiamiento en el cine peruano: el caso de las películas Papá youtuber, Recontra loca y Papá x tres - Rodríguez Albarracín, Ivette María Alejandra (2020)
In 2019, three Peruvian films of the comedy genre were released: “Papá Youtuber”, produced by Funny Games Films; “Recontra loca” produced by La Soga Producciones; and finally, “Papá x tres”, produced by Big Bang Films. The financing management modalities used by these three production companies and which allowed the making of his films, they have certain similarities. In the same way, since it is the same audiovisual genre, the launch process and the marketing strategies have a certain affinity. Therefore, the main objective of this research is to analyze the financing management modalities of these three production companies for the making of their films. A qualitative methodology was used, specifically, interviews and content analysis. These three film production companies serve as an example for future filmmakers, who seek to venture into Peruvian cinema, find different forms of financing for commercial cinema.